Effects of Mentha piperita on In Vitro Fermentation and Digestibility of Complete Rations for Small Ruminants - Bhat, A. R.; Ganai, A. M.; Ishfaq, A.; Masood, Danish; Sheikh, G. G.; Beigh, Y. A. (Indian Journal of Animal Nutrition, 2017)
The work was undertaken to study the effects of Mentha piperita (Pudina) on in vitro fermentation and digestibility using rumen liquor from sheep. The M. piperita was analysed for chemical composition. Different experimental rations were prepared with incorporation of M. piperita in the complete feed @ 0, 1, 2, 3, 4 and 5%. The digestibility improved (P< 0.05) at 3% addition in complete feed beyond which a significant (P